T cell responses to 60/65 kDa heat shock protein derived peptides in Turkish patients with Behçet's disease - (:unkn) unknown (My University, 2000)
OBJECTIVE: Sequence homology and cross reactivity between microbial and human heat shock proteins (HSP) led to the concept that HSP might be involved in the etiopathogenesis of Behçet's disease (BD). We investigated T cell responses to 8 synthetic peptides derived from the mycobacterial 65 kDa and homologous human 60 kDa HSP in patients with BD. METHODS: T cell proliferative responses to synthetic peptides were studied in 49 patients with BD and 46 disease (DC) and 34 healthy controls (HC) with 3H-thymidine uptake test. RESULTS: Positive T cell responses to one or more of the mycobacterial peptides were observed in 52% (12/23) of patients with BD compared with 17% (3/18) of DC (p = 0.02) and to homologous human peptides in 57% (13/23) of BD and 11% (2/18) of DC (p < 0.01). Responses to the mixtures of 4 mycobacterial peptides were also significantly higher in BD compared with controls (stimulation index in BD 4.7 +/- 3.5 vs DC 2.0 +/- 1.2, HC 1.6 +/- 0.4; BD vs DC and HC, p < 0.001). Similar elevated responses to the mixture of 4 human peptides was also observed in patients with BD (BD 3.4 +/- 2.3; DC 1.9 +/- 0.8; HC 1.4 +/- 0.6; BD vs DC, p < 0.01; BD vs HC, p < 0.001). CONCLUSION: These results suggest that cellular immunity against the 65 kDa mycobacterial and 60 kDa human HSP derived peptides is significantly increased in Turkish patients with BD compared to controls, as observed in the UK and Japan.
Keywords: Adult; Female; Humans; Middle Aged; Behcet Syndrome; Male; Molecular Sequence Data; Reference Values; Bacterial Proteins; T-Lymphocytes; Mycobacterium; Peptide Fragments; Cells, Cultured; Cell Division; Amino Acid Sequence; Chaperonin 60; Chaperonins